Use of dragging as organizer for conjecture validation (2009)
In this article, we report on a study centred on the teaching and learning of proof in which there is evidence that dragging becomes a source for significant student participation in the validation of conjectures. The findings highlight the teacher¿s use of dragging as an organizer of the activity, in cases when there are conjectures that students consider acceptable but for which they do not have the theoretical elements to validate them.